2012
DOI: 10.1029/2011jc007396
|View full text |Cite
|
Sign up to set email alerts
|

Processes setting the characteristics of sea surface cooling induced by tropical cyclones

Abstract: [1] A 1/2°resolution global ocean general circulation model is used to investigate the processes controlling sea surface cooling in the wake of tropical cyclones (TCs). Wind forcing related to more than 3000 TCs occurring during the 1978-2007 period is blended with the CORE II interannual forcing, using an idealized TC wind pattern with observed magnitude and track. The amplitude and spatial characteristics of the TC-induced cooling are consistent with satellite observations, with an average cooling of $1°C th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
206
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(225 citation statements)
references
References 88 publications
(125 reference statements)
19
206
0
Order By: Relevance
“…A fixed depth average has been justified by its simplicity and because the depth of mixing is only a weak function of the TC strength for strong storms [Lloyd and Vecchi, 2011;Vincent et al, 2012a]. However, we will show here that using a variable L leads to significant improvements in terms of variance explained in TC intensification.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A fixed depth average has been justified by its simplicity and because the depth of mixing is only a weak function of the TC strength for strong storms [Lloyd and Vecchi, 2011;Vincent et al, 2012a]. However, we will show here that using a variable L leads to significant improvements in terms of variance explained in TC intensification.…”
Section: Introductionmentioning
confidence: 98%
“…While the forecast of a TC's path has improved substantially over the past few decades, the prediction of its intensity remains challenging [Rappaport et al, 2012]. When over the ocean, vertical mixing induced by a TC entrains colder, deeper water into the relatively warm near-surface mixed layer, resulting in a cooling of the sea surface temperature (SST) [Price, 1981;Bender and Ginis, 2000;D'Asaro et al, 2007;Vincent et al, 2012aVincent et al, , 2012b. The decrease in SST is a negative feedback on the TC's intensity through its reduction in the flux of heat from the ocean to the atmosphere [Shay et al, 2000;Cione and Uhlhorn, 2003;Lloyd and Vecchi, 2011;Balaguru et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…What is not shown in Shay's figure is the horizontal advection by the ocean currents that move cold water from the rear part of the wake to the front and extend the width of the wake (Chen et al 2010: Vincent et al 2012. Using a two-way coupled model, Chen et al (2010) showed the distinct spatial separation among these three primary forcing terms that are generating the bulk of the cooling (Figure 2).…”
Section: A Formation Of the Cold Wakementioning
confidence: 99%
“…S trong winds associated with tropical cyclones (TCs) increase air-sea heat fluxes, favoring the intensification of storms, and generate vigorous vertical mixing in the upper ocean, stirring warm surface waters with colder waters below (1)(2)(3)(4)(5)(6). The wake produced by the passage of TCs is thus characterized by a surface cold anomaly and a subsurface warm anomaly (1-3, 6, 7).…”
mentioning
confidence: 99%